Comparing different types of web surveys - Silber, Henning (Metodološki zvezki, 2013)
This paper aims to compare different types of web surveys in terms of response behaviour and data quality. To do so, the data of four online samples, two online access panels, a student sample, and a generated mail sample randomly drawn from a systemically generated pool of email addresses were contrasted. To investigate expected sample differences in drop-out rates, non-response, and data quality, closed and open-ended questions of varying levels of sensitiveness were employed. The main findings were that the two access panels lead to lower item non-response, but especially when sensitive questions were asked, data quality problems were revealed. Moreover, the access panelists showed a tendency to take short-cuts in the response process and to edit their answers in favour of social desirability.
Keywords: Spletne ankete; Web surveys; Response rate; Stopnja odgovorov